2011
DOI: 10.1111/j.1365-2796.2010.02236.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietic protoporphyria in Sweden: demographic, clinical, biochemical and genetic characteristics

Abstract: Design. Cross-sectional questionnaire, biochemical and genetic study. Setting. Sweden.Subjects. Fifty-one Swedish individuals known in 2008 to have EPP confirmed by molecular diagnosis. There were no exclusion criteria; all patients were included in the demographic and genetic study. A total of 92% participants completed the questionnaire study and 82% the biochemical study.Results. The prevalence of EPP was 1 : 180 000. Nine novel ferrochelatase gene mutations were found. The most commonly reported age at ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
98
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(117 citation statements)
references
References 36 publications
12
98
1
6
Order By: Relevance
“…Recent studies (17,18) have shown that patients with erythropoietic protoporphyria have a severely reduced quality of life, which is partly explained by the long diagnostic delay, major restrictions on daily living and the fact that there are few treatment options. In light of the fact that several of the porphyrias may have long diagnostic delays, may cause severe and/or pronounced distress and are dependent on life-long follow-up, new studies are needed to assess the need for follow-up and help for porphyria patients at different stages of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies (17,18) have shown that patients with erythropoietic protoporphyria have a severely reduced quality of life, which is partly explained by the long diagnostic delay, major restrictions on daily living and the fact that there are few treatment options. In light of the fact that several of the porphyrias may have long diagnostic delays, may cause severe and/or pronounced distress and are dependent on life-long follow-up, new studies are needed to assess the need for follow-up and help for porphyria patients at different stages of life.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is diagnostically challenging, not only because it is very rare, but also because the clinical presentation may be a small child who cries and is agitated when exposed to the sun, without this being accompanied by distinct skin lesions (1). This study includes too few patients with erythropoietic protoporphyria to allow us to investigate whether time to diagnosis is shorter now than in the past, but the studies from Sweden and the UK have failed to demonstrate any change (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme deficiency is caused by mutations in the FECH gene which is located on chromosome 18q21.3. To date, 190 mutations responsible for EPP have been described [13,19,31].…”
Section: Erytropoietic Protoporphyriamentioning
confidence: 99%
“…Cholelithiasis due to gallstones containing protoporphyrin is reported in about 25% of EPP patients. Liver failure affects 2-5% of patients; many present iron deficiency with microcytic anemia and low vitamin D levels [1,13,31].…”
Section: Erytropoietic Protoporphyriamentioning
confidence: 99%
See 1 more Smart Citation